2015
DOI: 10.2298/zmspn1528029v
|View full text |Cite
|
Sign up to set email alerts
|

Diatom species composition in the Raska river (Southwestern Serbia)

Abstract: The paper presents data on the composition of epilithic diatoms in the Raska River. Samples were collected by scraping stone surfaces with a brush from 5 localities along the Raska River in April, June, August and November 2011 and March and May 2012. Diatom frustules were cleaned using cold acid method, and mounted on permanent slides. An investigation of the Raska River resulted in description of 106 diatom taxa. The most species rich genera are Navicula (10), Gomphonema (10) and Nitzschia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The most abundant genera were:Navicula, Gomphonemaa nd Nitzschia. This is to be expected, since researches in Serbia (Andrejić et al, 2012;Vidaković et al, 2015;Jakovljević et al, 2016aJakovljević et al, , 2016bVasiljević et al, 2017) and other countries (Hlúbiková et al, 2009;Sevindik & Kucuk, 2016;Noga et al, 2016) have shown that these three genera are dominant in the epilithic community.…”
Section: Biologymentioning
confidence: 80%
“…The most abundant genera were:Navicula, Gomphonemaa nd Nitzschia. This is to be expected, since researches in Serbia (Andrejić et al, 2012;Vidaković et al, 2015;Jakovljević et al, 2016aJakovljević et al, , 2016bVasiljević et al, 2017) and other countries (Hlúbiková et al, 2009;Sevindik & Kucuk, 2016;Noga et al, 2016) have shown that these three genera are dominant in the epilithic community.…”
Section: Biologymentioning
confidence: 80%
“…Fallacia lenzii (Hustedt) Lange-Bertalot (Fig. 3(19 16,17 Psammothidium bioretii;18,19 P. grischunum;[20][21][22][23]24,25 Achnanthidium druartii;[26][27][28][29]30,31 A. caledonicum;32,33 A. eutrophilum,34,35 A. crassum;36,37 A. straubianum. Scale bar=10 µm.…”
Section: Achnanthidium Caledonicumunclassified
“…The first diatom data in Serbia date from 1883 [16]. However, it was only in the second half of the 20 th century that extensive research into diatoms began [17][18][19][20][21], and in the last twenty years the number of new recorded diatom taxa for Serbian flora has increased [20][21][22][23][24]. The aim of this paper was to report new records of diatom taxa from different sites throughout Serbia in order to supplement the diatom checklist.…”
Section: Introductionmentioning
confidence: 99%